Econometrics informing natural resources management : selected empirical analyses - Koundouri, Phoebe, 1974- (Cheltenham, UK ; Northampton, Mass. : Edward Elgar Pub., 2004)
This fascinating book outlines the fundamental principles and difficulties that characterize the challenging task of using econometrics to inform natural resource management policies. The book offers a comprehensive overview of the broader picture of the state-of-the art in econometrics as applied to environmental and natural resource management.
Includes index.
nmn 15/05/13
Loans
Keywords: Natural resources -- Management -- Econometric models; Environmental economics